Diamondoid-based molecular junctions: a computational study. (7th November 2016) - Adhikari, Bibek; Sivaraman, Ganesh; Fyta, Maria
Abstract: In this work, we deal with the computational investigation of diamondoid-based molecular conductance junctions and their electronic transport properties. A small diamondoid is placed between the two gold electrodes of the nanogap and is covalently bonded to the gold electrodes through two different molecules, a thiol group and a N-heterocyclic carbene molecule. We have shown that the thiol linker is more efficient as it introduces additional electron paths for transport at lower energies. The influence of doping the diamondoid on the properties of the molecular junctions has been investigated. We find that using a nitrogen atom to dope the diamondoids leads to a considerable increase of the zero bias conductance. For the N-doped system we show an asymmetric feature of the I–V curve of the junctions resulting in rectification within a very small range of bias voltages. The rectifying nature is the result of the characteristic shift in the bias-dependent highest occupied molecular orbital state. In all cases, the efficiency of the device is manifested and is discussed in view of novel nanotechnological applications.